Inovação na gestão de processos patrimoniais de acervos bibliográficos físicos: estudo de caso das bibliotecas integrantes do Sistema de bibliotecas da Universidade Federal do Tocantins - Barreto, Isaias Cristino Esteves (UFT, 2021)
Public university libraries have the purpose of expanding and structuring their collections qualitatively designating to meet the informational needs of the academic and administrative community. The fulfillment of this purpose is consolidated through the acquisition, by the government or donations from the general public, of bibliographic materials, products, processes and services that constitute goods for the institutions that need to be managed according to the legal and administrative basis. In this context, the objective of this research is to propose a methodology (technical standard) that aims to innovate and qualify the patrimonial management of the physical bibliographic collections of the information units that are part of the UFT Library System (Sisbib / UFT). The methodological path was outlined by the case study method, which investigates a contemporary phenomenon within its context. The research counted with the participation of 8 subjects, being 1 general coordinator of the patrimony and 7 librarians of the Federal University of Tocantins that produced data from the collaboration in answering questionnaires. The analysis of the data generated was of an interpretative nature outlined from the literature review, document analysis and data survey. It was based on individual and collective reflections and on the production of knowledge presented in the responses generated after the application of the questionnaires and the other stages of the research. This research provided an identification of the strategies in use in the patrimonial management of libraries at the Federal University of Tocantins and it is possible to discern that despite all the efforts of the team, there are still a series of gaps to be filled. Through this recognition, it is concluded that changes in the practices currently adopted for asset management and innovation are urgent, enabling us to develop a methodology for asset management - MGP (Technical Standard) that may serve as a basis for further deepening and / or improvement .